2010
DOI: 10.1007/s11172-010-0209-x
|View full text |Cite
|
Sign up to set email alerts
|

EPR spectroscopy of thermally induced and light-induced spin transitions in heterospin exchange clusters of compounds Cu(hfac)2LR

Abstract: The review summarizes the results of EPR investigations of magneto structural anomalies occurring in exchange coupled copper nitroxide clusters belonging to the family of compounds Cu(hfac) 2 L R . The key features and potential of EPR spectroscopy in studies of such systems, the methods developed to determine the exchange constants, and experiments using the optical switching of magnetic parameters in the heterospin exchange clusters studied are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][33][34][35] As expected, the complexes reported herein contain chelating κ 2 -O,O'-bonded F 6 acac formally anionic groups with Cu-O bond lengths which are of the typical range (1.9-2.2 Å). The oxazoline ligand, predictably N-bonded, 4,5,[7][8][9][10][11][12]31 occupies a basal position with one of the F 6 acac O-atoms occupying the formal equatorial position of an idealised square pyramidal ligand arrangement.…”
Section: Compoundsupporting
confidence: 61%
See 1 more Smart Citation
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][33][34][35] As expected, the complexes reported herein contain chelating κ 2 -O,O'-bonded F 6 acac formally anionic groups with Cu-O bond lengths which are of the typical range (1.9-2.2 Å). The oxazoline ligand, predictably N-bonded, 4,5,[7][8][9][10][11][12]31 occupies a basal position with one of the F 6 acac O-atoms occupying the formal equatorial position of an idealised square pyramidal ligand arrangement.…”
Section: Compoundsupporting
confidence: 61%
“…This copper containing starting material has been extensively studied in coordination chemistry and materials science due to its ability to coordinate a variety of N-donor ligands which includes organic radicals, heterocycles, primary amines, etc. A wide variety of structural bonding motifs [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] have been observed in the resulting coordination compounds. …”
Section: Introductionmentioning
confidence: 99%
“…21,61,[72][73][74][75][76][77][78][79][80][81][82][83] The specific characteristics originate from predominant population of ground spin multiplet 72 and dynamic mixing (electron spin exchange) processes. 73 EPR of these compounds complements the magnetic susceptibility and X-ray techniques, and represents an efficient method for studying exchange interactions and coordination modes.…”
Section: Epr Study Of Breathing Crystalsmentioning
confidence: 99%
“…This unusual effect certainly deserved a special study, but the crystal structure of the compound was not studied below the transition point because the single crystals exploded below 30 K. 40 Later it was found, however, that all the magnetic effects described in, 36,[38][39][40] had the same nature and were associated with a structural phase transition, which was induced by the external treatment and changed the distances and angles between the paramagnetic centers in heterospin exchange clusters and hence the exchange-coupling energy. [19][20][21]38 Based on the accumulated data on the magnetochemical behavior of these heterospin complexes and their properties, it is clear that this is a widespread phenomenon and the spin-transition-like behavior is now recorded even in the case of insignificant structural rearrangements of heterospin solid phases during polymorphic transformations 41,42 .…”
mentioning
confidence: 99%
“…7,10,13,29 Due to this, one can trace the structure dynamics before and after the phase transition in these "breathing" 9À20 crystals. Previously, it was shown that varying an alkyl substituent in the pyrazole fragment of the paramagnetic ligand considerably affected the structure of the solid 7À10, 16,20,29 and hence the magnetic properties of the compounds. It was also reported that modification of coordination units by forming mixed-metal solid solutions was an effective tool for changing the magnetic properties of compounds.…”
Section: ' Introductionmentioning
confidence: 99%